Implementation of Sociocultural Based Character Education in Senior High School - Muhammad Rijal Fadli (LPPM Universitas Negeri Yogyakarta, 2021)
Abstract: The purpose of this study is to analyze the implementation of sociocultural (social-cultural)-based character education with the aim of providing empowerment in the world of education for the formation of national character based on socio-cultural values, at the high school education level. This sociocultural-based character education has been adapted to the goals of national education which focuses on teachers and developing skills and knowledge, as well as building the nation's character. The research uses qualitative methods with phenomenological design. Data collection techniques used observation techniques, interviews, FGD (focus group discussions), and documentation studies to obtain the observed data. Data analysis is guided by data reduction techniques, data presentation, and conclusion drawing. The result of this research shows that the implementation of sociocultural-based character education is referred to as an alternative solution and learning model to instill character values that consider the advantages of local/regional culture and the potential of socio-cultural values. Lampung, as one of the provinces of Indonesia, certainly has the uniqueness and characteristics of the traditional culture of Lampung, which is known as a friendly and heterogeneous community, so it is very relevant for planting and strengthening character education in high school. With the design of character education based on local sociocultural culture and implemented in an integrated manner in subjects. Keywords: Character Education, Sociocultural, Senior High School, Lampung.